2015
DOI: 10.1038/jcbfm.2014.237
|View full text |Cite
|
Sign up to set email alerts
|

Reference Region Modeling Approaches for Amphetamine Challenge Studies with [11C]FLB 457 and PET

Abstract: Detecting fluctuations in synaptic dopamine levels in extrastriatal brain regions with [11 C]FLB 457 and positron emission tomography (PET) is a valuable tool for studying dopaminergic dysfunction in psychiatric disorders. The evaluation of reference region modeling approaches would eliminate the need to obtain arterial input function data. Our goal was to explore the use of reference region models to estimate amphetamine-induced changes in [11 C]FLB 457 dopamine D2/D3 binding. Six healthy tobacco smokers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 30 publications
3
70
1
Order By: Relevance
“…Since the current BP ND values in target regions are relatively high (>15), a relatively large maximum difference in BP ND estimates by SRTM can be anticipated. Similar observations have previously been reported for several other radioligands, including [ 11 C]Cimbi-36, [ 11 C]WAY-100635 and [ 11 C]FLB 457 [24, 3335]. As for these established radioligands, reference tissue models may be considered for quantification of [ 11 C]Lu AE92686 binding in NHP studies in particular when multiple PET measurements are performed on the same subject such as in pharmacological challenge studies [32, 34, 36].…”
Section: Discussionsupporting
confidence: 88%
“…Since the current BP ND values in target regions are relatively high (>15), a relatively large maximum difference in BP ND estimates by SRTM can be anticipated. Similar observations have previously been reported for several other radioligands, including [ 11 C]Cimbi-36, [ 11 C]WAY-100635 and [ 11 C]FLB 457 [24, 3335]. As for these established radioligands, reference tissue models may be considered for quantification of [ 11 C]Lu AE92686 binding in NHP studies in particular when multiple PET measurements are performed on the same subject such as in pharmacological challenge studies [32, 34, 36].…”
Section: Discussionsupporting
confidence: 88%
“…The VCTR was administered the day prior to amphetamine administration (pre-amphetamine condition) and again 100 minutes following amphetamine administration (post-amphetamine condition). This time point was chosen to fall within or near the peak plasma amphetamine level [87]. Figure 1C illustrates the timing of PET scans and VCTR task sessions.…”
Section: Star Methodsmentioning
confidence: 99%
“…Although few studies suggest small specific binding of [ 11 C]FLB457 in cerebellum, no change in cerebellar distribution volume was observed following challenges with amphetamine and methylphenidate . Previous studies with [ 11 C]FLB457 have successfully used SRTM with cerebellum as a reference region (eg, Ko et al, Mizrahi et al), and a recent study showed that SRTM is a valid modelling approach to measure the percentage change in BP ND ( italicBPND=1BPNDStress/BPNDControl) with [ 11 C]FLB457 . Right and left ROIs were pooled together to create a single TAC used to derive the BP ND .…”
Section: Methodsmentioning
confidence: 99%